Adoption of Mobile Augmented Reality as a Campus Tour Application - Andri, Chairil; Hazim Alkawaz, Mohammed; Bibo Sallow, Amira (International Journal of Engineering and Technology, 2018)
Campus tours are among the opportunities for colleges and universities to show their environment, facilities and achievement to the visitors or prospective students. Along with the advancement technology of mobile devices, smartphone and tablet have created new possibilities for the institutions to create mobile application which is integrated with augmented reality to engage campus visitors in new and more intuitive ways. Augmented reality can superimpose a virtual object or information into real world environments. Many universities are utilizing this technology as a mobile campus touring application to make the visitors become familiar with the campus through the self-guided devices. This paper presents a survey of mobile campus tour application based augmented reality at various universities as well as the features of each application such as information about points of interest, location search, navigation, 3D campus building, campus events, ecological environment, virtual tour, and outdoor games. Â